Hubungan Antara Penggunaan Cephalosporin dengan Peningkatan APTT Dan PT Pada Pasien Kardiovaskular Di Antara Pasien Di Rumah Sakit Pemerintah Bengkulu - Diana Laila Ramatillah; Rahelia Purba; Atika Rahima Mahyani; Mohamed Hasan Elnaem; Baharudin Ibrahim; Syed Azhar Syed Sulaiman (Fakultas Farmasi Universitas Andalas, 2024)
The interaction that occurs between warfarin and antibiotics is a pharmacokinetic interaction which cause bleeding. This study aims to determine whether there is a relationship between the use of cephalosporins and an increase in APTT and PT in cardiovascular patients. This retrospective observational study employs case-control analysis to examine APTT and PT features in cardiovascular patients receiving single anticoagulant or anticoagulant + cephalosporin therapy for the period JulyDecember 2020. The sampling method used in this study is a convenient sampling method that meets the inclusion and exclusion criteria. Analysis of the data used is Logistic Regression. The study found among 65 male and 15 female, 40 patients used anticoagulant, and another 40 patients used anticoagulant and cephalosporine. Among 40 patients who used combination anticoagulant and cephalosporin, 22 of them had experienced of increasing APTT and PT. Cephalosporins showed a significant correlation with APTT and PT, with a P-value of 0.015. From this study, it can be concluded that the use of cephalosporins increases in APTT and PT values in cardiovascular patients who are given anticoagulant drugs and cephalosporins